Analisis determinan kinerja pasar modal (IDX30) di Indonesia - Hary Saputra Sundoro; Grace Putlia; Jessica Vonnie Lie (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
Indonesia has a capital market called the Indonesian Stock Exchange (IDX). IDX performance can be measured from existing indices and one of them is the IDX30 index. IDX 30 performance can be influenced by several factors such as macroeconomic variables and CPO prices. This research aims to determine movements in capital market performance in Indonesia caused by influencing factors. The VECM method will be used in this research. The research period starts from 2019 to June 2023. The result of this research is that CPO prices and inflation have a positive influence, while reference interest and exchange rates have a negative influence on IDX30 performance in the short and long term. The performance response of the IDX30 is most influenced by the IDX30 variables themselves. Public interest statements The research hopes that the relevant parties, especially the government, issuers and investors can take the necessary policies. The results of this research can be a reference material in predicting capital market movements in Indonesia, especially the IDX30 index, which is caused by factors that influence it, such as macroeconomics and CPO prices.